Language proficiency and homeownership: Evidence from U.S. immigrants - Marc-André Luik; Max Friedrich Steinhardt; Simon Voss (Freie Universität Berlin, School of Business & Economics, 2023)
In this paper we deliver first causal evidence on the relationship between immigrant host country language proficiency and homeownership. Using an instrumental variable strategy, we find a substantial positive impact of language skills on the propensity to own a home and the quality of housing. While this effect is mediated by education and household income, our estimates also speak in favor of a direct effect. Our results highlight the importance of host-country-specific human capital and, in particular, language proficiency for socio-economic assimilation.
urn:nbn:de:kobv:188-refubium-38475-8
Keywords: J11; J13; J61; R21; Z13; 330; language; immigrants; assimilation; homeownership